Workload of nurses working in the operating theatre - Katarzyna Tomaszewska; Bożena Majchrowicz; Grażyna Hejsak (Kazimierz Wielki University, 2020)
Introduction: An operating theatre is a place where life-saving treatments are often performed. Nurses working in this place must not only be competent in terms of knowledge and skills, but strong physically and mentally. The article deals with the problem of workload of perioperative and anesthetist nurses. Aim of the study: comparison of workload of perioperative and anesthetist nurses working in the operating theatre. Material and methods: The research group consisted of 207 perioperative and anesthetist nurses employed in the operating theatres of hospitals in the Podkarpackie Voivodeship in the first half of 2019. The research method was a diagnostic survey conducted by means of a questionnaire. Statistical analysis was carried out using the SPSS programme and all the relationships are statistically significant when p≤0.05. Results and conclusions: Research has shown that nurses working in the operating theatre experience stress during work in the operating theatre due to responsibility for the patient and exposure to occupational exposure, contact with chemical agents and skeletal load.